Hydrogen‐Etched Bifunctional Sulfur‐Defect‐Rich ReS2/CC Electrocatalyst for Highly Efficient HER and OER - Pang, Qing‐Qing; Niu, Zhu‐Lin; Yi, Sha‐Sha; Zhang, Shuo; Liu, Zhong‐Yi; Yue, Xin‐Zheng (Small (Weinheim an der Bergstrasse, Germany), 2020)
The design on synthesizing a sturdy, low‐cost, clean, and sustainable electrocatalyst, as well as achieving high performance with low overpotential and good durability toward water splitting, is fairly vital in environmental and energy‐related subject. Herein, for the first time the growth of sulfur (S) defect engineered self‐supporting array electrode composed of metallic Re and ReS2 nanosheets on carbon cloth (referred as Re/ReS2/CC) via a facile hydrothermal method and the following thermal treatment with H2/N2 flow is reported. It is expected that, for example, the as‐prepared Re/ReS2‐7H/CC for the electrocatalytic hydrogen evolution reaction (HER) under acidic medium affords a quite low overpotential of 42 mV to achieve a current density of 10 mA cm−2 and a very small Tafel slope of 36 mV decade−1, which are comparable to some of the promising HER catalysts. Furthermore, in the two‐electrode system, a small cell voltage of 1.30 V is recorded under alkaline condition. Characterizations and density functional theory results expound that the introduced S defects in Re/ReS2‐7H/CC can offer abundant active sites to advantageously capture electron, enhance the electron transport capacity, and weaken the adsorption free energy of H* at the active sites, being responsible for its superior electrocatalytic performance. The S‐defect‐rich ReS2/CC electrocatalyst for highly efficient hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is constructed. The as‐prepared Re/ReS2‐7H/CC affords the overpotentials of 44 and 290 mV at 10 mA cm−2 under alkaline condition for HER and OER, respectively, a small cell voltage of 1.30 V in alkaline medium in the two‐electrode system, which are superior to pristine ReS2/CC.